2019
DOI: 10.3390/su11236592
|View full text |Cite
|
Sign up to set email alerts
|

A Nutritional Evaluation of Insect Meal as a Sustainable Protein Source for Jumbo Quails: Physiological and Meat Quality Responses

Abstract: The use of insect meals in place of soybean meal in diets is critical for sustainable intensification of poultry production, but the utility of this alternative dietary protein source is unknown for the Jumbo quail. Therefore, this study investigated the effect of partial substitution of soybean with black soldier fly larvae (BSFL) meal on feed intake, physiological, and meat quality parameters of Jumbo quails. Three hundred and fifteen mixed-gender quails (53.8 ± 5.19 g live-weight) were reared on five isonit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 27 publications
5
27
2
Order By: Relevance
“…These findings were in line with those of many authors who reported a lack of differences on growth performance of various poultry species when soybean meal was replaced with various insect meals ( Maurer et al., 2016 ; Biasato et al., 2016 ; Cullere et al., 2018 ; Elahi et al., 2020 ). Contrary to our findings, several studies have reported that the inclusion of insect meals improves the bird performance ( Mareko, Nsoso, Mosweu, Mokate, & Madibela, 2010 ; Mbhele, Mnisi, & Mlambo, 2019 ; Zadeh, Kheiri, & Faghani, 2019 ). Nonetheless, it is worth noting that the nutritive value of these meals vary by species, life stage and rearing condition, which could explain the wide variability of the reported results ( Zadeh, Kheiri, & Faghani, 2019 ).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…These findings were in line with those of many authors who reported a lack of differences on growth performance of various poultry species when soybean meal was replaced with various insect meals ( Maurer et al., 2016 ; Biasato et al., 2016 ; Cullere et al., 2018 ; Elahi et al., 2020 ). Contrary to our findings, several studies have reported that the inclusion of insect meals improves the bird performance ( Mareko, Nsoso, Mosweu, Mokate, & Madibela, 2010 ; Mbhele, Mnisi, & Mlambo, 2019 ; Zadeh, Kheiri, & Faghani, 2019 ). Nonetheless, it is worth noting that the nutritive value of these meals vary by species, life stage and rearing condition, which could explain the wide variability of the reported results ( Zadeh, Kheiri, & Faghani, 2019 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Despite the nutritional properties of MW, its effect on quail meat quality has not been investigated. We found that inclusion of MWM had no effect on meat pH, temperature, water retention, cooking and thawing losses, which was in agreement with the findings of Mbhele, Mnisi, and Mlambo (2019) and Elahi et al. (2020) , who reported a lack of dietary effect on meat quality.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations